TrkB kinase activity maintains synaptic function and structural integrity at adult neuromuscular junctions - Mantilla, Carlos B. (American Physiological Society, 2014)
Activation of the tropomyosin-related kinase receptor B (TrkB) by brain-derived neurotrophic factor acutely regulates synaptic transmission at adult neuromuscular junctions (NMJs). The role of TrkB kinase activity in the maintenance of NMJ function and structure at diaphragm muscle NMJs was explored using a chemical-genetic approach that permits reversible inactivation of TrkB kinase activity in TrkB(F616A) mice by 1NMPP1. Inhibiting TrkB kinase activity for 7 days resulted in significant, yet reversible, impairments in neuromuscular transmission at diaphragm NMJs. Neuromuscular transmission failure following 2 min of repetitive phrenic nerve stimulation increased from 42% in control to 59% in 1NMPP1-treated TrkB(F616A) mice (P = 0.010). Recovery of TrkB kinase activity following withdrawal of 1NMPP1 treatment improved neuromuscular transmission (P = 0.006). Electrophysiological measurements at individual diaphragm NMJs documented lack of differences in quantal content in control and 1NMPP1-treated mice (P = 0.845). Morphological changes at diaphragm NMJs were modest following inhibition and recovery of TrkB kinase activity. Three-dimensional reconstructions of diaphragm NMJs revealed no differences in volume at motor end plates (labeled by α-bungarotoxin; P = 0.982) or presynaptic terminals (labeled by synaptophysin; P = 0.515). Inhibition of TrkB kinase activity by 1NMPP1 resulted in more compact NMJs, with increased apposition of presynaptic terminals and motor end plates (P = 0.017) and reduced fragmentation of motor end plates (P = 0.005). Recovery of TrkB kinase activity following withdrawal of 1NMPP1 treatment resulted in postsynaptic remodeling likely reflecting increased gutter depth (P = 0.007), without significant presynaptic changes. These results support an essential role for TrkB kinase activity in maintaining synaptic function and structural integrity at NMJs in the adult mouse diaphragm muscle.